CEP55 as a promising biomarker and therapeutic target on gallbladder cancer - Huang, Maotuan; Zhong, Fuxiu; Chen, Mingyuan; Hong, Lingju; Chen, Weihong; Abudukeremu, Xiahenazi; She, Feifei; Chen, Yanling (Frontiers in Oncology, 2023)
Gallbladder cancer (GBC) is a highly malignant biliary tumor with poor prognosis. As the existing therapies for advanced metastatic GBC are rarely effective, there is an urgent need to identify more effective targets for treatment. In this study, we employed bioinformatics analysis to screen out five hub genes of GBC, namely PLK1, CEP55, FANCI, NEK2 and PTTG1. Further GBC tissue validation showed that CEP55 expression was elevated in GBC tissues and related to the negative prognosis for patients. We showed that CEP55 knockdown significantly inhibited the proliferation of GBC cells by CCK8, colony formation assay and EDU staining. Moreover, flow cytometry, western blot, immunofluorescence and alkaline comet assay were performed to elucidate cell cycle, apoptosis and the underlying mechanism of the anticancer effect of CEP55 knockdown. After CEP55 knockdown, GBC cells was arrested in G2/M phase and appeared DNA damage. In addition, there was a marked increase of apoptosis of GBC cells in the siCEP55group. Besides, in vivo, CEP55 inhibition attenuated the growth and promoted apoptosis of GBC cells. Mechanically, the tumor suppressor effect of CEP55 knockdown is associated with dysregulation of AKT and ERK signaling network. Collectively, these data not only demonstrate that CEP55 is identified as a potential independent predictor crucial to the diagnosis and prognosis of gallbladder cancer, but also reveals the possibility for CEP55 as a promising target to be used in the treatment of GBC.